Penser la musique, Écouter les images. Lectures de Cahiers d’art, Jazz et Documents sur le jazz et le cinéma américains - Diane Turquety (Les Cahiers de l'École du Louvre)
From 1926 to 1931, Cahiers d’art, Jazz and Documents, magazines on art or culture more generally, covered American jazz and cinema in a new way. Marked by popular culture, the United States and the “exotic” touch embodied by the American black community, these entertainments were elevated to the rank of new forms of artistic expression, vectors of an ideal modernity. Jazz and talkies then became, gradually and in different ways, new objects of aesthetic study. Above all, in the eyes of this Parisian press, they constituted crucibles of values likely to regenerate a post‑war Europe in decline.